Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 23 May 2017, 02:51

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# A boat traveled upstream a distance of 90 miles at an

Author Message
Director
Joined: 03 Sep 2006
Posts: 875
Followers: 7

Kudos [?]: 891 [0], given: 33

A boat traveled upstream a distance of 90 miles at an [#permalink]

### Show Tags

23 Jun 2007, 03:04
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

A boat traveled upstream a distance of 90 miles at an average speed of (v-3) miles per hour and then traveled the same distance downstream at an average speed (v+3) miles per hour. if the trip upstream took half an hour longer than the trip downstream, how many hours did it take the boat to travel downstream?
Director
Joined: 09 Aug 2006
Posts: 757
Followers: 1

Kudos [?]: 210 [0], given: 0

### Show Tags

23 Jun 2007, 04:42
Upstream:
D = 90 m
S= (v-3) m/hr
Let T = t

Downstream:
D=90
S=(v+3) m/hr [let this be statement 1]
T = t-1/2 = (2t-1)/2 [let this be statement 2]

D=ST
Since D is the same upstream & downstream:
=> t(v-3) = (v+3)(2t-1)/2
=> 2tv-6t = 2tv+6t-v-3
=> v+3=12t or t=(v+3)/12 [let this be statement 3]

Using the value of t from statement 3 in statement 2 we get T=(V-3)/12
D= S * T
=> 90= (v+3)(v-3)/12
=>v^2=1089
=>v=33 [let this be statement 4]

Therefore, when going downstream:
D= 90
S = v+3 = 33+3 = 36 m/hr
T = 90/36 = 2.5 hrs.

Not sure if the above is correct. Even if it is, I'm sure there's a much simpler way to solve this.
Director
Joined: 03 Sep 2006
Posts: 875
Followers: 7

Kudos [?]: 891 [0], given: 33

### Show Tags

23 Jun 2007, 06:14
GK_Gmat wrote:
Upstream:
D = 90 m
S= (v-3) m/hr
Let T = t

Downstream:
D=90
S=(v+3) m/hr [let this be statement 1]
T = t-1/2 = (2t-1)/2 [let this be statement 2]

D=ST
Since D is the same upstream & downstream:
=> t(v-3) = (v+3)(2t-1)/2
=> 2tv-6t = 2tv+6t-v-3
=> v+3=12t or t=(v+3)/12 [let this be statement 3]

Using the value of t from statement 3 in statement 2 we get T=(V-3)/12
D= S * T
=> 90= (v+3)(v-3)/12
=>v^2=1089
=>v=33 [let this be statement 4]

Therefore, when going downstream:
D= 90
S = v+3 = 33+3 = 36 m/hr
T = 90/36 = 2.5 hrs.

Not sure if the above is correct. Even if it is, I'm sure there's a much simpler way to solve this.

Your approach is perfect and answer is absolutely correct. But what "I" or "we" need is a fast approach to be able to solve it within 2 minutes!

Anyone with some fast approach?
23 Jun 2007, 06:14
Display posts from previous: Sort by